Pengaruh Konformitas dan Konsep Diri (Prestige) terhadap Minat Beli Online Mahasiswa dengan Perilaku Konsumtif Mahasiswa sebagai Variabel Pemediasi - Shita Lusi Wardhani; Bambang Setia Wibowo (Jurnal Manajemen dan Bisnis Indonesia, 2018)
This study examined the influence of conformity and self-concept to consumptive behavior and its impact to online shopping intention. This study is the integration of previous studies to determine the effect of simultaneous between variables. Respondents of this study were 142 university students who have ever seen e-commerce advertisements on electronic media participated in this reseach. There are several findings in this study. First, conformity has positive influence to the consumptive behavior. Second, self-concept has postive effect to consumptive behavior. Third, consumptive behavior has positive effect to online shopping intention. Fourth, consumptive behavior perfect mediate the effect of conformity and self-concept to the online shopping intention. Keywords : conformity, self-concept, consumptive behavior, online shopping intention